Effectiveness of multidisciplinary interventions to improve blood culture efficiency and optimize antimicrobial utilization - Zihuan Li; Keqi Hu; Tian Wang; Baohong Liu; Wen Zheng; Jianqun Zhou; Ting Fan; Maorui Lin; Guanwen Lin; Sujuan Li; Cuiqiong Fan (Frontiers Media S.A., 2024)
BackgroundThe low positive rate of blood cultures often leads to downstream consequences. We present a summary of multidisciplinary interventions implemented by a tertiary referral hospital to improve blood culture efficiency and optimize antimicrobial usage.MethodsWe evaluated the knowledge, attitude, and practice (KAP) of healthcare workers in a tertiary care hospital before and after intervention using a questionnaire. A multidisciplinary team was formed to implement the intervention, defining roles, standardizing procedures, continually improving education and feedback, and establishing incentive mechanisms. Regular quality control assessments are conducted on the responsible departments.ResultsFollowing the intervention, the median submission time for blood culture specimens was reduced from 2.2 h to 1.3 h (p < 0.001). Additionally, the intervention group showed significant (p < 0.05) increases in rates of positivity (9.9% vs. 8.6%), correct timing (98.7% vs. 89.6%), correct processing (98.1% vs. 92.3%), reduced contamination rates (0.9% vs. 1.4%), and disqualification rates (1.3% vs. 1.7%). The delivery rate of therapeutic antibacterial increased (16.1% vs. 15.2%), and the consumption of restrictive grade antimicrobial also significantly increased (26.7% vs. 22.9%). The intervention measures led to a substantial improvement in awareness and compliance with KAP of blood culture collection in the hospital. Hospital-wide antimicrobial usage deceased by 10.7% after intervention.ConclusionA multidisciplinary collaborative model proves effective in improving blood culture efficiency and optimizing antimicrobial usage.